Analisis Penjadwalan Ulang pada Proyek Pembangunan Gedung Asisten Pidana Militer (ASPIDMIL) - Ikhlas, Muhammad; Amalia; Ridha, Muhammad; Sriana, Tety (Universitas Iskandar Muda, 2026)
Construction delays are a common challenge in building projects and are often caused by inaccurate scheduling, limited resources, and ineffective project management. The ASPIDMIL Building project experienced a significant delay, with an actual duration of 244 days compared to the planned 180 days. This study evaluates rescheduling using the Critical Path Method (CPM) and the Precedence Diagram Method (PDM) to identify critical activities, assess acceleration potential, and compare cost efficiency. The analysis shows that CPM reduces the project duration to 220 days, while PDM provides a greater improvement with a shortened duration of 209 days. Correspondingly, labor costs decrease by 4.35% under CPM and 9.13% under PDM. These results demonstrate that PDM is more effective for complex building projects that require overlapping activities and flexible logical relationships.